Healthcare and non-healthcare professionals’ knowledge about nutrition in older adults: a cross-sectional study - Marijana Matek Sarić; Tamara Sorić; Ana Sarić; Paula Smoje; Anamarija Rozić; Marina Matković; Sanja Zoranić; Marija Ljubičić (BMC Public Health)
Abstract Background Malnutrition frequently affects older adults, increasing their risk for numerous diseases, as well as healthcare costs. Therefore, nutritional assessment and appropriate nutritional support addressed to meet individual nutritional needs and prevent malnutrition and its consequences should be a fundamental part of healthcare for older adults. This study aimed to compare the knowledge of nutrition guidelines for older adults between healthcare and non-healthcare professionals working with older adults. Methods The study was conducted during May and June 2021 using a validated “Knowledge of nutrition guidelines for older adults” questionnaire designed by Andrija Stampar Teaching Institute of Public Health, Croatia. The study participants were recruited from various institutions providing care for older adults in Split-Dalmatia and Dubrovnik-Neretva County. The final convenience sample consisted of 214 participants (163 healthcare professionals and 51 non-healthcare professionals). The obtained results were analyzed using descriptive and inferential statistics. The associations between participants’ characteristics and knowledge about the importance of nutrition in disease prevention and treatment, the assessment of nutritional status in older adults, and clinical nutrition were analyzed using multiple linear regression models. Results Participants’ overall knowledge of nutrition guidelines for older adults was moderate in both groups, with healthcare professionals scoring a median of 7.0 (IQR = 1.0) and non-healthcare professionals scoring a median of 6.0 (IQR = 2.0). Compared to non-healthcare professionals, healthcare professionals had lower knowledge about the importance of nutrition in disease prevention and treatment (β = − 0.16; p = 0.024). No statistically significant differences were found between healthcare and non-healthcare professionals in the level of knowledge about the assessment of nutritional status in older adults (β = − 0.02; p = 0.769) and clinical nutrition (β = 0.08; p = 0.267). Conclusions This study highlights gaps in knowledge regarding dietary guidelines for older adults among healthcare and non-healthcare professionals working with this specific population group. These findings suggest that targeted educational programs might be needed to improve understanding of geriatric nutrition.